PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Euis Ajizah; Mulyani Mulyani (Universitas La Tansa Mashiro, 2019)
This research talk about profitability is aimed at obtaining information related to possibility whether probality is related by current ratio, debt to asset ratio and debt to equity ratio. The research was conducted at the property and real astate companies at Indonesian Stock Exhange (ISE) by using survey method with regretion applied in testing hypotesis, thirty nine datas were selected as samples by purposive sampling from forty nine. The result indicated that There is an influence between current ratio on profitability, There is an influence between debt to asset ratio on profitability, There is an influence between debt to equty ratio on profitability and There is a significant influence between current ratio, debt to asset ratio,debt to equty ratio on profitability. Therefore current ratio, debt to asset ratio,debt to equty ratio. should be put into consideration in developing profitability